Patient satisfaction and oral health-related quality of life 10 years after implant placement - Wang-Kuffer, Yan; Bäumer, Daniel; Ozga, Ann-Kathrin; Körner, Gerd; Bäumer, Amelie (BMC oral health, 2021)
Implant survival and implant success (freedom of biologic complications) are important factors in assessing the success of implant therapy. However, these factors are not the only determinants. Patients’ satisfaction also plays a very important role in daily practice. Therefore, the aim of this study was to assess patients’ satisfaction regarding function (phonetics, chewing comfort, stability, cleanability) and aesthetics in patients treated with XiVE and Frialite implants in a private periodontal practice ten years after implant placement. Furthermore, oral health-related quality of life (OHRQoL) was evaluated.
Gesehen am 22.02.2021